Analisis Penerapan Teori Kecerdasan Majemuk dalam Pembelajaran di Sekolah Alam Cikeas - Yusi Srihartini; Azwar Abdurakhman; Muhammad Hafiz; Noor Albar; Fariz Fudla Fasih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the application of the theory of multiple intelligences at the Cikeas Nature School. This research will examine various activities and learning methods used to develop students' multiple intelligences. In addition, this research will analyze the impact of applying this theory on the student learning process, including motivation, participation and learning outcomes as well as discussing the supporting factors and challenges faced in its implementation. This research uses a qualitative approach and case study with data collection techniques in the form of literature reviews, observations, interviews and documentation. The research results show that the application of the theory of multiple intelligences at the Cikeas Nature School has brought significant changes in teaching methods and has had a positive impact in increasing student motivation and participation in learning. Students feel more engaged and enthusiastic when they can learn in a way that suits their learning style. This research also found several supporting factors and challenges in implementing the theory of multiple intelligences at the Cikeas Natural School. Among these supporting factors are: a conducive learning environment, the diversity of teaching methods used, and the involvement of parents and the community. Meanwhile, some of the challenges are: the lack of understanding of some teachers in implementing the theory of multiple intelligences and challenges in the evaluation and assessment system.